Peranan Komunikasi Pemasaran Pariwisata Melalui Pemanfaatan E-Tourism Marketing untuk Meningkatkan Niat Berkunjung Wisatawan - Gampo Haryono; Albetris Albetris (Ekonomis: Journal of Economics and Business, 2022)
The tourism sector also brings social, economic, and environmental, natural resources, and cultural impacts that are increasingly prudent and prudent. One of the facilities developed is the concept of e-tourism. E-Tourism provides information on tourist destinations with various needs for tourists. This research aims to find out the role of tourism marketing communication through the utilization of e-tourism marketing to Increase Tourist Visiting Intentions. So as to increase tourist visits in Kerinci Regency in the new normal era in the Covid 19 era. Respondents in this study were all visitors from destinations in tourist attractions in Kabuten Kerinci Jambi Province. The number is unknown and can be said to be in infinite categories. Sampling techniques in this study use non probability techniques, namely incidental sampling techniques. Sampling techniques in this study use non probability techniques, namely incidental sampling techniques. The number of samples taken in this study used the lemeshow formula so that 96 samples were obtained in the study. The results of the study obtained results from the coefficient of determination is from E Tourism influenced by the variable promotion, e-WOM and advertising by 91%. While the coefficient of determination from the variables Promotion, e-WOM and advertising and e-tourism to visit intention is 9.3%.